Pengaruh Quick Ratio, Long Term Debt to Equity Ratio (LTDER) dan Net Profit Margin (Npm) Terhadap Harga Saham pada Perusahaan Sub Sektor Farmasi yang Terdaftar di BEI (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Quick Ratio (QR), Long-Term Debt to Equity Ratio (LTDER), and Net Profit Margin (NPM) on stock prices of pharmaceutical subsector companies listed on the Indonesia Stock Exchange (IDX). The study employed a quantitative method with an associative approach. The population consisted of 15 pharmaceutical subsector companies, while the sample was selected using purposive sampling, resulting in 3 companies observed during the 2020–2024 period with a total of 15 observations. Secondary data were obtained from corporate financial statements and analyzed using multiple linear regression with SPSS version 22. The results indicate that, partially, Quick Ratio has a significant effect on stock prices, Long-Term Debt to Equity Ratio has no significant effect on stock prices, and Net Profit Margin significantly affects stock prices. Simultaneously, Quick Ratio, Long-Term Debt to Equity Ratio, and Net Profit Margin have a significant effect on stock prices. The coefficient of determination (R²) of 79.2% indicates that stock price variations can be explained by the three independent variables, while the remaining 20.8% is influenced by other factors outside the scope of this study